Augmentative and Alternative Communication and Communication Skills in Deaf Students: A Systematic Review - Ita Rodiawati; Elsa Efrina; Marlina Marlina; Antoni Tsaputra; Ita Rodiawati; Elsa Efrina; Marlina Marlina (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Limited access to auditory input can create significant barriers for Deaf and Hard-of-Hearing students, particularly in language acquisition and social communication. This study aims to systematically review empirical research on the use of AAC systems in enhancing the communication abilities of hearing-impaired students. Articles were retrieved from the Scopus database and by using Preferred Reporting Items for Systematic Reviews and Meta-Analyses procedures. A total of five empirical studies met the inclusion criteria and were analyzed through qualitative analysis. Results showed that Augmentative and Alternative Communication treatments led to gains in initiations, single-word spoken-language production, receptive and expressive vocabulary, single-word reading accuracy, social communication skills. Results found were positive with both low and high technology approaches, although benefited most when used in conjunction with speech-language therapy and early intervention programs. Implementation obstacles included insufficient support for training teachers and providing places to go online. In general, these results indicated that Augmentative and Alternative Communication systems contributed to the communication development process, enhancing language acquisition skills and serving social participation in students with hearing disabilities. It was suggested that additional larger-scaled empirical studies with experimental designs should be conducted to reinforce the existing evidence.